Peran Kepala Sekolah Dalam Implementasi Kurikulum Merdeka - Adha, Wahyu Arief; Fadhila, Siska (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2023)
The merdeka curriculum is a curriculum that is gradually implemented by the Indonesian government. Many reforms have occurred in this curriculum, so that educational units experience problems in adapting and implementing the merdeka curriculum in their respective educational units. The principal as a pillar of leadership in the elementary school education unit has a very large contribution to the implementation of the merdeka curriculum. This research will explain the role of the principal in driving schools, who implementing merdeka curriculum and the challenges that arise in implementing an merdeka curriculum in elementary schools.